Peripheral tachykinins and the neurokinin receptor NK1 are required for platelet thrombus formation - Jones, Sarah; Tucker, Katherine L.; Sage, Tanya; Kaiser, William J.; Barrett, Natasha E.; Lowry, Philip J.; Zimmer, Andreas; Hunt, Stephen P.; Emerson, Michael; Gibbins, Jonathan M. (Blood, 2008)
Platelets play an important role in hemostasis, with inappropriate platelet activation being a major contributor to debilitating and often fatal thrombosis by causing myocardial infarction and stroke. Although current antithrombotic treatment is generally well tolerated and effective, many patients still experience cardiovascular problems, which may reflect the existence of alternative underlying regulatory mechanisms in platelets to those targeted by existing drugs. In this study, we define a role for peripherally distributed members of the tachykinin family of peptides, namely substance P and the newly discovered endokinins A and B that are present in platelets, in the activation of platelet function and thrombus formation. We have reported previously that the preferred pharmacologically characterized receptor for these peptides, the NK1 receptor, is present on platelets. Inhibition or deficiency of the NK1 receptor, or SP agonist activity, resulted in substantially reduced thrombus formation in vitro under arterial flow conditions, increased bleeding time in mice, and a decrease in experimentally induced thromboembolism. Inhibition of the NK1 receptor may therefore provide benefit in patients vulnerable to thrombosis and may offer an alternative therapeutic target.